2015
DOI: 10.1093/humrep/dev042
|View full text |Cite
|
Sign up to set email alerts
|

AMH mutations with reduced in vitro bioactivity are related to premature ovarian insufficiency

Abstract: The study was performed thanks to funding from the 'Fondation Erasme'. No conflicts of interest are declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Therefore, the age-related increase in primordial follicle activation may arise from a reduction in inhibitory signals rather than an increase in activation-promoting regulators. This is further supported by mutations in the AMH and AMHR2 genes that are associated with primary ovarian insufficiency or decreased age at menopause (Kevenaar et al 2007, Park et al 2014, Alvaro Mercadal et al 2015. Across the lifespan, increased rates of primordial follicle activation tend to coincide with lower levels of inhibitors of primordial follicle activation, including AMH.…”
Section: Amh Expression Patterns Are Consistent With Primordial Follimentioning
confidence: 91%
“…Therefore, the age-related increase in primordial follicle activation may arise from a reduction in inhibitory signals rather than an increase in activation-promoting regulators. This is further supported by mutations in the AMH and AMHR2 genes that are associated with primary ovarian insufficiency or decreased age at menopause (Kevenaar et al 2007, Park et al 2014, Alvaro Mercadal et al 2015. Across the lifespan, increased rates of primordial follicle activation tend to coincide with lower levels of inhibitors of primordial follicle activation, including AMH.…”
Section: Amh Expression Patterns Are Consistent With Primordial Follimentioning
confidence: 91%
“…In chicken, the expression level of AMH was related to the growth of small follicles [37]. Several evidence has also shown that AMH inhibited the activation of primordial follicles [38], attenuated the rate of follicular growth [39] and inhibited follicular recruitment [40], suggesting the inhibitory action of AMH in the selection and growth of small follicles. It was also found that the expression level of AMH in GCs of the 4–10 mm follicles was higher than that in those of the F5–F1 follicles, suggesting that AMH might play a negative role in geese follicle recruitment and selection.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma AMH level is one of the criteria used to diagnose polycystic ovary syndrome (PCOS) 20 , which results in an anovulation, and subsequent infertility, in women of reproductive age. Besides, AMH is an excellent marker of ovarian reserve, as a decrease in AMH level is typically accompanied by ovarian senescence 21 , 22 . Also, AMH can inhibit the process of primordial follicle recruitment and follicle development 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, AMH is an excellent marker of ovarian reserve, as a decrease in AMH level is typically accompanied by ovarian senescence 21 , 22 . Also, AMH can inhibit the process of primordial follicle recruitment and follicle development 22 .…”
Section: Discussionmentioning
confidence: 99%